Joint tests for dynamic and spatial effects in short dynamic panel data models with fixed effects and heteroskedasticity - YANG, Zhenlin (Institutional Knowledge at Singapore Management University, 2021)
Simple and reliable tests are proposed for testing the existence of dynamic and/or spatial effects in fixed-effects panel data models with small T and possibly heteroskedastic errors. The tests are constructed based on the adjusted quasi scores (AQS), which correct the conditional quasi scores given the initial differences to account for the effect of initial values. To improve the finite sample performance, standardized AQS tests are also derived, which are shown to have much improved finite sample properties. All the proposed tests are robust against nonnormality, but some are not robust against cross-sectional heteroskedasticity (CH). A different type of adjustments is made on the AQS functions, leading to a set of tests that are fully robust against unknown CH. Monte Carlo results show excellent finite sample performance of the standardized versions of the AQS tests.